The prevalence of musculoskeletal disorder and the association with risk factors among auto repair mechanics in Klang Valley, Malaysia - Ahmad Nasaruddin, Ahmad Faisal; Mohd Tamrin, Shamsul Bahri; Karuppiah, Karmegam (Tehran University of Medical Sciences, 2014)
Background: The primary objective of this study was to determine the association between risk factors and the prevalence of musculoskeletal disorder (MSD) among auto repair mechanics in Klang Valley, Malaysia.